PENGARUH PENGEMBANGAN KARIR, KOMPENSASI DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION (Studi pada Karyawan PT. Mega Pasanggrahan Indah Unit Cinere Bellevue Mall) - Anggriawan, Ferri; Herminingsih, Anik (Universitas Mercu Buana, 2025)
This study aims to analyze the effect of career development, compensation and organizational commitment on turnover intention. The population in this study were 116 employees of PT. Mega Pasanggrahan Indah Unit Cinere Bellevue Mall. The sample used is 54 employees, calculated based on the Slovin formula. Sampling method using simple random sampling. This research is a type of causal associative research. The instrument of this research used a questionnaire. The data analysis method used in this research is the Smart PLS version 3.0 application. The results of this study prove that career development has a negative and significant effect on turnover intention, compensation has a negative and significant effect on turnover intention, and organizational commitment has a negative and significant effect on turnover intention.Keywords: Career Development; Compensation; Organizational Commitment; Turnover Intention.